Development Analysis In Jonday Furniture Product Innovation In The Modern Era - Sulthan Adikusuma; Pipin Sukandi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This research aims to find out the development of Jonday's innovation in the field of furniture in the era of modernization, this research uses qualitative methods in order to find out how much impact furniture has on a person's effectiveness in carrying out a daily activity in the modernization era, and how big the opportunity for Jonday furniture to be able to develop its business to the international market. Based on the research results, it can be concluded that the furniture products created by Jonday can help people to be more productive and effective in working and studying. So the innovation of Jonday furniture has different benefits from its competitors in the field of furniture in this modern era, the difference in products created by Jonday furniture with other competitors is that the products produced prioritize the usefulness and beauty of a product, and have an ordering system according to what each consumer wants. With the product customization system without a minimum order, it makes consumers feel benefited, and the models created adjust to the current era that continues to develop, and become furniture that supports the creation of smarthome. From the business aspect, this product is an innovation that can be a business opportunity in the future because this product has benefits that can increase the effectiveness and productivity of every community in carrying out their activities that require furniture.